The voices of medieval Bulgaria, seventh-fifteenth century : the records of a bygone culture - Petkov, Kiril, 1964- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2008)
This volume is the first comprehensive collection to gather together the records of the medieval Bulgarian centuries in English translation. Stone annals, works of religious instruction, anti-heretical treatises, apocrypha, royal charters, as well as numerous graffiti and marginal notes, shed abundant light onto a major cultural tradition of the European southeast from the seventh to the fifteenth century. Produced by Bulgarians of all walks of life, the evidence testifies, among other things, to the unique features of Bulgarian historical consciousness, political custom, and religious sensibility as well as the country’s conformity to the broad currents of medieval Europe’s cultural development and evolution. The volume furnishes a fundamental reading for all those interested in the historical destiny of the “other” Europe.